INTERNET OF THINGS-BASED WATER PIPE LEAK DETECTION SYSTEM - Anhar; Widyatma, Daffa Hanif; Syafrianti, Ery; Yuliani Putri, R.A Rizka Qori (Elektrika, 2025)
Leaks in pipelines are a very important issue and should not be underestimated in terms of handling and resolution. If a leak in a pipe is not addressed immediately, it can cause adverse effects, such as a decrease in water flow efficiency, and in some conditions, it can even stop the flow of water completely. Therefore, a water pipe leak detection system is needed to be implemented in homes. In this research, a prototype of a water pipe leak detection system consisting of a 4-branch and a T-branch was built to simulate piping conditions in users' homes. This system uses a water flow meter sensor as a leak detection sensor by comparing the difference in water discharge readings between sensors. me-ter water flow sensor is a sensor that is very suitable for this task. The water flow meter sensor works on the principle of hall effect and can read the water flow rate precisely and accurately with a reading accuracy of 9.9%. The system is IoT connected to blynk for easy monitoring and maintenance by the user. From 10 experiments conducted, the system successfully detected leaks with 100% success rate. The delay that occurs when sending data from the microcontroller to blynk is 67 ms.